Comparative study of magnetic resonance defaecography and evacuation proctography in the evaluation of obstructed defaecation. (June 2017) - Zafar, A.; Seretis, C.; Feretis, M.; Karandikar, S.; Williams, S. C.; Goldstein, M.; Chapman, M.
Abstract: Aim: Obstructed defaecation syndrome is a common condition of multifactorial aetiology and requires specialized evaluation. Accurate and reproducible pelvic floor imaging is imperative for multidisciplinary decision‐making. Evacuation proctography (EP) and magnetic resonance defaecography (MRD) are the main imaging modalities used to assess dynamic pelvic floor function. The aim of this prospective study was to compare the findings and acceptability of MRD and EP in the same cohort of patients. Method: This was a prospective comparative study of MRD vs EP in 55 patients with obstructed defaecation syndrome in a single National Health Service Foundation Trust. Results: Fifty‐five patients were recruited and underwent both EP and MRD. Detection rates for rectocoele were similar (82% vs 73%, P = 0.227), but EP revealed a significantly higher number of trapping rectocoeles compared to MRD (75% vs 31%, P < 0.001). EP detected more rectal intussusceptions than MRD (56% vs 35%, P = 0.023). MRD appeared to underestimate the size of the identified rectocoele, although it detected a significant number of anatomical abnormalities in the middle and anterior pelvic compartment not seen on EP (1.8% enterocoele, 9% peritoneocoele and 20% cystocoele). Patients achieved higher rates of expulsion of rectal contrast during EP compared to MRD, but this difference was not significant (76% vs 64% in MRD, P = 0.092). Of the two studies, patients preferred MRD. Conclusions: MRD provides a global assessment of pelvic floor function and anatomical abnormality. MRD is better tolerated by patients but it is not as sensitive as EP in detecting trapping rectocoeles and intussusceptions.